Online Pedagogical Training during the COVID-19 Outbreak: Responses, Challenges, and Contributions - Adnan Gribiea; Zenab Elsana (MDPI AG, 2024)
The COVID-19 pandemic led to the widespread closure of educational systems, prompting a shift to online learning methods for instructors and students in higher education institutions. This study explores how pedagogical instructors supported accessibility to online pedagogical training during this crisis. This qualitative investigation employed a case study methodology, focusing on the high school training program at a multicultural college of education in Israel. Semi-structured interviews were conducted with six pedagogical instructors to explore their roles as educators, their oversight of pedagogical training, the implementation of didactic workshops and practical work, and their responses to the COVID-19 pandemic across technological, pedagogical, and emotional dimensions. Findings underscore the critical role of pedagogical instructors during the shift to remote learning. They facilitated communication using digital tools among pre-service teachers, coaching professors, and students, akin to conducting an orchestra with multiple participants. Amid widening educational, technical, and social disparities among students, pedagogical instructors and their pre-service teachers played a pivotal role in curriculum adaptation and crisis management within the school setting.